Analysis of the feeding habits in cyclists of the Spanish national mountain bike team - Som, A.; Zabala, M.; Ramirez-Lechuga, J.; Muros, J. J.; Sánchez-Sánchez, E.; Sánchez-Munoz, C. (Archivos de medicina del deporte, 2008)
Athlete`s correct feeding pattern can determine a better sport performance, being considered crucial the correct caloric and nutritional intake. Objective: The aim of the study was to know the feeding habits of the members of the Spanish mountain bike national team to detect weaknesses and/or strengths. Method: Fourty cyclists -Cadet, Junior, U-23, and elite categories- participated in the study. The sample was divided into two groups attending to the hours spent on training and competition level (25 Cadet and Junior- age: 16.68±0.99; weight: 62.94±7.01; height: 172.48±7.03; BMI: 21.10±1.29; body fat %: 11.92±1.98; Muscle mass %: 49.89±1.45; residual mass %: 23.46±1.31-, and 15 U-23 and elite- age: 25.33±4.25; weight: 60.24±6.97; height: 168.05±7.05; BMI: 21.28±1.48; body fat %: 11.49±1.42; muscle mass %: 54.31±1.42; residual mass %: 22.18±1.62-). A specific questionnaire and individual interview was used to get the data and a latest descriptive and contrast between groups (Wilcoxon) statistical analyses was developed. Results: In the younger group 76% of the sample did 3 intakes per day, while for the higher group was 60% (p=0.348); four intakes per day were carried out by 4% of the subjects of the younger group and 13.3% for U-23 and elite; five intakes were for the 20% of the younger group and for 26.7% of the U-23 and elite. The 64% of the younger eat between meals, while this value was significantly reduced to 26% for U23 and elite (p=0.024). Also, 56% of the younger used to eat "fast food" products, while for the higher group this was significantly reduced to a 20% of the U-23 and elite (p=0.028). Considering different aspects, in the younger group (cadet and Junior) 76% of the subjects show a considered "bad" feeding habit, while in the U-23 and elite group this value was significantly lower -36%- (p=0.003). Conclusion: Results show the different and worse feeding habits showed by the younger (Cadet and Junior) in contrast to the U-23 and elite cyclists. It is not known if this is due to the age and the new tendencies or may be to the professional habits that could appear later in a more professional context. It is recommended to dedicate more time educating the younger from the earlier ages to get better feeding habits -i.e. including theoretical-practical formation in training camps for athletes and parents-